Current perspectives in Sudanese and Nubian archaeology : a collection of papers presented at the 2018 Sudan Studies Research Conference, Cambridge /: a collection of papers presented at the 2018 Sudan Studies Research Conference, Cambridge. (2021) - Unknown
No abstract available